The evolving role of imaging in sports injury management - Paluch, Anna; Grylowska, Gabriela; Tryba, Michał; Gunia, Katarzyna; Adamczyk, Aleksandra; Banasik, Mateusz; Rebizant, Marcin; Żak, Agata; Palak, Andrzej; Ignatowicz, Anna (Quality in Sport, 2026)
Background. Sports injuries constitute a significant health problem in professional and recreational sports. With the growing popularity of physical activity and intensified training, a growing incidence of musculoskeletal injuries has been observed. Imaging diagnostics plays a crucial role in the evaluation of these injuries, enabling assessment of anatomical structures, detection of pathological changes, and monitoring of treatment. Aim. The aim of this study was to review scientific reports on the role of imaging modalities in improving the quality of medical care for athletes. Material and methods. Publications available PubMed database published between 2016 and 2026 were analyzed. The article discusses the most important imaging methods used in the diagnosis of sports injuries, including conventional radiography, ultrasonography, magnetic resonance imaging, and computed tomography. Their characteristics, clinical applications, and diagnostic limitations are presented. Particular attention was paid to the importance of magnetic resonance imaging and ultrasonography in the evaluation of soft tissues, as well as the role of computed tomography in the diagnosis of complex bone injuries. The paper also presents current directions in imaging diagnostics, including the application of artificial intelligence. Results. The analysis of the available literature indicates that the appropriate selection of imaging modalities significantly improves the quality of care for athletes by increasing diagnostic accuracy, shortening the time required to establish a diagnosis, and enabling more precise treatment planning as well as a return to sports activity. Conclusions. Modern imaging diagnostics plays a fundamental role in sports medicine. Proper use of radiography, ultrasonography, magnetic resonance imaging, and computed tomography supports effective diagnosis and treatment of sports injuries, contributing to safer and faster return to sports activity.